1995
DOI: 10.1093/clinids/21.6.1390
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Meningitis in Children: Prognostic Indicators and Outcome

Abstract: We studied the outcome of pneumococcal meningitis in 83 children who were admitted to a referral hospital and whose meningitis was diagnosed between 1970 and 1994. The median age of the children was 8 months. The most frequently isolated capsular serotypes and/or serogroups of Streptococcus pneumoniae were 6, 14, 18, 19, and 23. Twenty-nine children (35%) were referred by other hospitals. A mortality rate of 17% (primary referrals, 7%; secondary referrals, 35%) was observed. At discharge, 25 survivors (36%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
0
9

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 35 publications
13
69
0
9
Order By: Relevance
“…In 2 studies of bacterial meningitis before the widespread use of PCV7, neurologic sequelae associated with S pneumoniae were reported in 20% to 40% of children at the time of hospital discharge. 11,12 It is unknown whether the frequency of severe neurologic sequelae and adverse outcomes has changed in the era of widespread PCV7 use as a consequence of the change in infecting serotypes. Our objective in the current study was to describe the epidemiology, serotypes, clinical outcomes, and sequelae of culture-confirmed pediatric pneumococcal meningitis before and after PCV7 licensure in Utah.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 studies of bacterial meningitis before the widespread use of PCV7, neurologic sequelae associated with S pneumoniae were reported in 20% to 40% of children at the time of hospital discharge. 11,12 It is unknown whether the frequency of severe neurologic sequelae and adverse outcomes has changed in the era of widespread PCV7 use as a consequence of the change in infecting serotypes. Our objective in the current study was to describe the epidemiology, serotypes, clinical outcomes, and sequelae of culture-confirmed pediatric pneumococcal meningitis before and after PCV7 licensure in Utah.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Previous pediatric studies have reported neurologic sequelae in 20% to 40% of children with bacterial meningitis. 11,25,31 The higher incidence of neurologic sequelae documented in this cohort of children may be due to our ability to capture long-term followup data (median follow-up period: 3.1 years) through the shared electronic data warehouse of Intermountain Healthcare, which is used by all consulting pediatric neurologists for these patients. Developmental delay was documented in 37% of survivors, persistent seizures in 31%, and hearing loss in 29%.…”
Section: Figurementioning
confidence: 99%
“…a Bos et al conducted a expert panel meeting in 1999 with representatives of the pediatric departments of most academic hospitals in the Netherlands. Table 3 Estimated mean and standard error for parameters used in the multivariate probabilistic sensitivity analysis with the appropriate references Parameter description Mean SE Vaccine efficacy against IPD at age 4-11 months-partially vaccinated individuals a [13] 0.857 0.2551 Vaccine efficacy against IPD after age 12 months-fully vaccinated individuals a [13] 0.939 0.0482 The effectiveness of the vaccine against episodes of otitis media (all causative agents) a [13] 0.064 0.0122 The effectiveness of the vaccine against clinical pneumonia (all causative agents) a [28] 0.06 0.0242 Reduction in total cases of IPD in unvaccinated age-group 20-39 a [16] 0.32 0.0408 Reduction in total cases of IPD in unvaccinated age-group 40-64 a [16] 0.08 0.0357 Reduction in total cases of IPD in unvaccinated age-group 65 and older a [16] 0.18 0.0332 Mortality of pneumococcal meningitis cases in children (population age mean 8 months) b [3] 0.169 0.0409 Mortality of pneumococcal bacteremia cases in children (population age < 15 years old) b [4] 0.06 0.0061 Mortality of pneumococcal meningitis cases in adults b [27] 0.304 0.0245 Mortality of bacteremia cases in adults b [26] 0.259 0.036 Serotype coverage of PCV7 of meningitis cases in the Netherlands b [21] 0.671 0.025 Serotype coverage of PCV9 of meningitis cases in the Netherlands b [21] 0.683 0.0247 Serotype coverage of PCV10 of meningitis cases in the Netherlands b [21] 0.782 0.0219 Serotype coverage of PCV13 of meningitis cases in the Netherlands b [21] 0.861 0.0184 Serotype coverage of PCV7 of bacteremia cases in the Netherlands b [21] 0.595 0.0256 Serotype coverage of PCV9 of bacteremia cases in the Netherlands b [21] 0.682 0.0243 Serotype coverage of PCV10 of bacteremia cases in the Netherlands b [21] 0.78 0.0216 Serotype coverage of PCV13 of bacteremia cases in the Netherlands b [21] 0 The distribution parameters are calculated by method of moments estimation. This requires an estimate of the mean and the standard error (SE).…”
Section: Web Interfacementioning
confidence: 99%
“…Invasive Pneumococcal Disease (IPD) is associated with high mortality rates [3,4] and may cause severe lifelong complications [5,6]. Non-invasive pneumococcal disease causes a high burden to society due to the high incidence of infection-related disease, such as otitis media and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-positive extracellular bacterium Streptococcus pneumoniae (pneumococcus) is the most common pathogen in adults and, despite antibiotic therapy, it has the highest mortality of all meningitis-causing agents: 4-16% in children and up to 60% in adults (2)(3)(4). Furthermore, pneumococcal meningitis causes the highest rates of neurologic sequelae (5), with long-term disabilities reported in 27-57% of survivors (6)(7)(8). The processes underlying pathogenesis in BM are complex, with contributions from both bacteria and host, but the immune response is believed to be a key factor (9)(10)(11).…”
mentioning
confidence: 99%